The process of process innovation : a case study of a finance firm in Asia. - Leong, Tak Keong. (2010)
The purpose of this dissertation is to use the case study method to gain insight of the innovation process based on Kanter's model of Innovation Tasks. Idea generation, coalition building, idea realization and diffusion are the four major tasks identified in the Kanter's model of Innovation Tasks. These task, and its determinants, were analyzed in detail through a case study of a process innovation, i.e., the new investment trading submission process in ACME Insurance that is made possible via a revolutionary digital pen and paper (DPP) technology. The case study reveals that it is possible for both the idea generation task and coalition building task to happen in tandem, instead of sequentially. In addition, the diffusion task is the most crucial part of the innovation process. Similary, the environmental determinants of the diffusion task, which has most influential effect on the success of the innovation, is often overlooked and under researched. This case study shows that even an excellent innovation idea with a state-of-the-art technology, managed to sail through smoothly throughout the innovation process, can result in setback during its diffusion.